Current status and factors affecting digital transformation at private drug retail establishments in Dong Nai province in 2025 - Minh, Trinh Hong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Digital transformation (DT) in our country is currently an urgent requirement for all sectors, including the pharmaceutical industry. There have been studies on the issue of DT in the manufacturing and distribution sectors, but there has not been a study in the drug retail sector. Therefore, identifying the factors that impact the activities DT implementation at private drug retail establishments is essential in the current period. Objectives: To assess the current status and determine the factors influencing the results of DT implementation and the acceptance of DT in private drug retail establishments. Materials and Methods: A convenience sampling method will be used for professional managers or staff at private drug retail establishments in Bien Hoa city, Dong Nai province, surveyed using a cross-sectional descriptive method in April 2025. Results: The DT implementation results and DT acceptance (Dependent variable) of 375 out of 1,200 currently operating private drug retail establishments were evaluated, seven groups of independent variables were identified (1. Characteristics of the survey participants; 2. The role of DT; 3. Competence of professional managers; 4. Competence of employees; 5. Competence of the facility; 6. Legal policies and 7. Customer needs) has been statistically tested to determine the effect on the dependent variable. Conclusion: Based on the research findings, recommendations are made for retailers to enhance their capabilities in the DT process and for regulatory agencies to implement policies for DT activities at private drug retail establishments.